Chemical composition and antioxidant activity of essential oil from leaves and rhizomes of Curcuma angustifolia Roxb. Issue 18 (17th September 2017) - Jena, Sudipta; Ray, Asit; Banerjee, Anwesha; Sahoo, Ambika; Nasim, Noohi; Sahoo, Suprava; Kar, Basudeba; Patnaik, Jeetendranath; Panda, Pratap Chandra; Nayak, Sanghamitra
Abstract: The essential oil extracted from rhizome and leaf of Curcuma angustifolia Roxb. (Zingiberaceae) was characterised by gas chromatography-mass spectrometry (GC-MS). The GC-MS analysis revealed the presence of 32 and 35 identified constituents, comprising 92.6% and 92% of total leaf and rhizome oil, respectively. Curzerenone (33.2%), 14-hydroxy- δ -cadinene (18.6%) and γ -eudesmol acetate (7.3%) were the main components in leaf oil. In rhizome oil, curzerenone (72.6%), camphor (3.3%) and germacrone (3.3%) were found to be the major constituents . Antioxidant capacities of oil were assessed by various methods, 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and reducing power ability (RPA). Based on the results, the leaf oil showed more antioxidant potential as compared to rhizome oil and reference standards (ascorbic acid and butylated hydroxytoluene (BHT)). Thus, the leaf essential oil of C. angustifolia can be used as an alternative source of natural antioxidant. Abstract :